Correlation of Parental Perception and Its Components with Attachment Style and Tendency to Communicate with the Opposite Sex in Veterans’ Daughters - M. Bazoolnejad; S. Robatmili (طب جانباز, 2018)
Aims: One of the factors damaging the family structure is the disability of a family member. Disability can be caused by events such as war; it may sometimes affect the senior family member, the father, and the children are also affected by this problem. The present study was conducted to evalualte the correlation of parental perception and its components with attachment style and tendency to communicate with the opposite sex in veterans’ daughters. Instruments and Methods: In this descriptive-correlational study, 77 veteranschr('39') daughters in Tehran, Iran were selected by voluntary sampling method. The research tools consisted of Parental Bonding Instrument (PBI), Adult Attachment Questionnaire (AAQ), and Tendency to Opposite Sex Questionnaire. The data were analyzed by SPSS 23, using Pearson correlation coefficient test. Findings: There was a positive correlation between parental perception (r=0.80) and the components of attempts to dependency (r=0.87) and emotional relationship (r=0.91) with tendency to the opposite sex, and there was a negative correlation between the components of indifference (r=-0.90) and encouragement for independence (r=-0.84) with tendency to the opposite sex. Also, the attachment style and parental perception (r=-0.85) had a negative correlation with the components of attempts to dependency (r=-0.92) and emotional relationship (r=-0.93), and had a positive correlation with the components of indifference (r=0.92) and encouragement for independence (r=0.89). Attachment style and tendency to the opposite sex (r=-0.92) had a negative correlation (p<0.01), too. Conclusion: Parental perception has a negative correlation with attachment styles and a positive correlation with the tendency to communicate with the opposite sex.